The political economy of industrial policy in post-apartheid South Africa: a comparative case study analysis of Brazil and South Korea - Modisaotsile, Botlhale Phurulla (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
South Africa is a country that has experienced premature deindustrialisation due to its inability to move out of middle-income status. The role of industrial policy in South Africa is pivotal to taking the country to greater economic heights and a higher-income status. South Africa's historical context indicates that the country experienced its highest GDP growth rates during the apartheid economy. Since the demise of apartheid, the post-apartheid economy has experienced poverty and economic inequality that the South African government cannot eradicate. This thesis addresses the failure of South Africa to overcome premature deindustrialisation, and it discusses the state of the political economy and economic growth in a pre-apartheid and post-apartheid context. The thesis also addressed the significance of industrial policy through the establishment of the Industrial Policy Action Plan (IPAP). The shortcomings and successes of IPAP form a critical part of the research and present an analysis of different economic sectors. This thesis also assesses the state of industrial policy using two countries as case studies: Brazil and South Korea.
Keywords: Industrial policy -- South Africa; South Africa Economic conditions 1991-; Korea (South) Economic conditions; Brazil Economic conditions; Apartheid -- South Africa; Political economy; Deindustrialization